Antibody-mediated delivery of LIGHT to the tumor boosts natural killer cells and delays tumor progression. Issue 1 (1st January 2021) - Stringhini, Marco; Mock, Jacqueline; Fontana, Vanessa; Murer, Patrizia; Neri, Dario
ABSTRACT: LIGHT is a member of the tumor necrosis factor superfamily, which has been claimed to mediate anti-tumor activity on the basis of cancer cures observed in immunocompetent mice bearing transgenic LIGHT-expressing tumors. The preclinical development of a LIGHT-based therapeutic has been hindered by the lack of functional stability exhibited by this protein. Here, we describe the cloning, expression, and characterization of five antibody-LIGHT fusion proteins, directed against the alternatively spliced extra domain A of fibronectin, a conserved tumor-associated antigen. Among the five tested formats, only the sequential fusion of the F8 antibody in single-chain diabody format, followed by the LIGHT homotrimer expressed as a single polypeptide, yielded a protein (termed "F8-LIGHT") that was not prone to aggregation. A quantitative biodistribution analysis in tumor-bearing mice, using radio-iodinated protein preparations, confirmed that F8-LIGHT was able to preferentially accumulate at the tumor site, with a tumor-to-blood ratio of ca. five to one 24 hours after intravenous administration. Tumor therapy experiments, performed in two murine tumor models (CT26 and WEHI-164), featuring different levels of lymphocyte infiltration into the neoplastic mass, revealed that F8-LIGHT could significantly reduce tumor-cell growth and was more potent than a similar fusion protein (KSF-LIGHT), directed against hen egg lysozyme and serving as negative control of irrelevant specificity in the mouse. At a mechanistic level, the activity of F8-LIGHT was mainly due to an intratumoral expansion of natural killer cells, whereas there was no evidence of expansion of CD8 + T cells, neither in the tumor, nor in draining lymph nodes. Abbreviations : CTLA-4: Cytotoxic T-lymphocytes-associated protein 4; EGFR: Epidermal growth factor receptor; HVEM: Herpesvirus entry mediator; IFNγ: Interferon-gamma; LIGHT: Lymphotoxin, exhibits inducible expression and competes with HSV glycoprotein D for binding to herpesvirus entry mediator, a receptor expressed on T lymphocytes; LTβR: Lymphotoxin beta receptor; NF-κB: Nuclear factor "kappa-light-chain-enhancer" of activated B cells; NK: Natural killer cells; PD-1: Programmed cell death protein 1; PD-L1: Programmed death-ligand 1; TNF: Tumor necrosis factor.